2020
DOI: 10.48550/arxiv.2005.08502
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVI White Paper

Hannah Alsdurf,
Edmond Belliveau,
Yoshua Bengio
et al.

Abstract: The SARS-CoV-2 (Covid-19) pandemic has resulted in significant strain on health care and public health institutions around the world. Contact tracing is an essential tool for public health officials and local communities to change the course of the Covid-19 pandemic. Standard manual contact tracing of people infected with Covid-19, while the current gold standard, has significant challenges that limit the ability of public health authorities to minimize community infections. Personalized peer-to-peer contact t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 75 publications
0
22
0
Order By: Relevance
“…To the best of our knowledge, no other work has studied the interaction between unemployment, COVID-19, and policy interventions. Existing public health research has focused on many aspects of COVID-19, including augmenting epidemiological models for COVID-19 (37,38), and analyzing contact-tracing in agent-based simulations (39), and evaluating the efficacy of various public health policy interventions (7,40,41). An analytical approach to policy design showed that the elasticity of the fatality rate to the number of infected is a key determinant of an optimal response policy (8,42).…”
Section: Case Study: Optimizing Public Health and The Economy During ...mentioning
confidence: 99%
“…To the best of our knowledge, no other work has studied the interaction between unemployment, COVID-19, and policy interventions. Existing public health research has focused on many aspects of COVID-19, including augmenting epidemiological models for COVID-19 (37,38), and analyzing contact-tracing in agent-based simulations (39), and evaluating the efficacy of various public health policy interventions (7,40,41). An analytical approach to policy design showed that the elasticity of the fatality rate to the number of infected is a key determinant of an optimal response policy (8,42).…”
Section: Case Study: Optimizing Public Health and The Economy During ...mentioning
confidence: 99%
“…Similarly, studies based on population such as polling or pharmaceutical trials have quantified uncertainties based on the quantity and quality of their samples. It is also possible to train on simulators, as in climate sciences [Rasp et al, 2018] or in epidemiology [Alsdurf et al, 2020], and some of them provide their estimations' uncertainty based on the simulation procedure and the inclusion of real measurements in the model.…”
Section: Heteroscedastic Noisy Labels In Regressionmentioning
confidence: 99%
“…1. The presented model has strong empirical confirmation in research of complex natural systems, such as the fight against the COVID-19 pandemic [4] [5], in the treatment of cardiac diseases [6] and in the Systems Earth Science [7]. In this article will be considered the application of this architecture to creation of new artificial systems with the aid of systematic approach.…”
Section: Introductionmentioning
confidence: 98%